2009
DOI: 10.1002/lt.21924
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of an automated pupillometer for assessing and monitoring recipients of liver transplantation

Abstract: Pupil examination has been used as a basic measure in critically ill patients and has great importance for the prognosis and management of disease. An automated pupillometer is a computer-based infrared digital video system by which the accuracy and precision of the pupil examination are markedly improved. We conducted an observational study of pupil assessment with automated pupillometry in clinical liver transplantation settings, including pretransplant evaluations and posttransplant surveillance. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…In critically ill patients, two preliminary studies found that the measurement of pupillary size with an automated pupillometer was more accurate than standard pupillary examination using a manual pen light [16,17]. Yan et al [18], in a larger cohort of liver transplant patients, found that peri-operative pupillary abnormalities measured with quantitative pupillometry were associated with neurological complications. Behrends et al [19], in a small cohort of 30 patients, found that quantitative pupillary reactivity performed during cardio-pulmonary resuscitation was associated with early survival.…”
Section: Introductionmentioning
confidence: 99%
“…In critically ill patients, two preliminary studies found that the measurement of pupillary size with an automated pupillometer was more accurate than standard pupillary examination using a manual pen light [16,17]. Yan et al [18], in a larger cohort of liver transplant patients, found that peri-operative pupillary abnormalities measured with quantitative pupillometry were associated with neurological complications. Behrends et al [19], in a small cohort of 30 patients, found that quantitative pupillary reactivity performed during cardio-pulmonary resuscitation was associated with early survival.…”
Section: Introductionmentioning
confidence: 99%
“…Meeker et al 12) reported that inter-examiner disagreement regarding the pupillary reaction was 39% for manual examinations compared with 1% for automated pupillometers. Hence, studies to define the relationship between clinical manifestations and PLR determined by automated pupillometer have been conducted in various fields 1 2 5 6 7 9 15 17 18) .…”
Section: Discussionmentioning
confidence: 99%
“… 15) In emergency medicine, research revealed that the presence of PLR, determined by automated pupillometer in patients with "fixed" pupils according to manual examinations, could be associated with early survival and a favorable neurological status in the recovery period 11) . Automated pupillometers were also used to assess the prognosis of patients receiving a liver transplantation 18) . Some anesthesiologists and pharmacologists have shown that automated pupillometers could be used to quantify the PLR, which can be affected by drugs and hence can provide proper information about the responses to these drugs 6 9 17) .…”
Section: Discussionmentioning
confidence: 99%
“…11 Loss of pupillary function can signify brain herniation owing to uncal compression of ciliary fibers of cranial nerve III. However, loss of pupillary function may be caused by metabolic abnormality in late stages of HE.…”
Section: Neurologic Assessment In Overt Hepatic Encephalopathymentioning
confidence: 99%